HUBUNGAN TINGKAT AKTIVITAS FISIK TERHADAP DEPRESI PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN VETERAN JAKARTA - Jihan Ari Utami (2022)
Background: Physical activity provides many physical health benefits, for example, increased functional capacity, reduced risk of disease, improved body composition, and weight loss. Previous research has also revealed that there are psychological benefits of physical activity, including improved mood and decreased depression and anxiety. In addition, physical activity has far-reaching effects on quality of life. Physical activity greatly affects the physical and mental health of humans. Objective: The purpose of this study was to determine the relationship between levels of physical activity and depression in students of the Faculty of Health Sciences UPN Veteran Jakarta. Methods: the research method used is correlational quantitative with a cross sectional approach. A total of 328 students of the Faculty of Health Sciences UPN Veteran Jakarta participated in this study, the parameters used were the IPAQ-SF (International Physical Activity Questionnaire Short Form) to assess the level of Physical Activity and the BDI II questionnaire (Beck Depression Inventory II) to assess the level of depression. Results: Based on the results of data processing using SPSS 25.0, it was found that as many as 207 of 328 respondents (63.1%) did not experience depression, after the correlation test was carried out, the correlation coefficient of Spearman's Rho physical activity and depression was p = - 0.426 with a significance value of p = 0.000. Conclusion: The conclusion obtained based on this study is that there is a relationship between levels of physical activity and depression in students of the Faculty of Health Sciences UPN Veteran Jakarta.